A Carbapenem-Resistant Pseudomonas aeruginosa Isolate Harboring Two Copies of bla(IMP-34) Encoding a Metallo-β-Lactamase - Tada, Tatsuya (PLoS One, 2016)
A carbapenem-resistant strain of Pseudomonas aeruginosa, NCGM1984, was isolated in 2012 from a hospitalized patient in Japan. Immunochromatographic assay showed that the isolate was positive for IMP-type metallo-β-lactamase. Complete genome sequencing revealed that NCGM1984 harbored two copies of bla(IMP-34), located at different sites on the chromosome. Each bla(IMP-34) was present in the same structures of the class 1 integrons, tnpA(ISPa7)-intI1-qacG-bla(IMP-34)-aac(6')-Ib-qacEdelta1-sul1-orf5-tniBdelta-tniA. The isolate belonged to multilocus sequence typing ST235, one of the international high-risk clones. IMP-34, with an amino acid substitution (Glu126Gly) compared with IMP-1, hydrolyzed all β-lactamases tested except aztreonam, and its catalytic activities were similar to IMP-1. This is the first report of a clinical isolate of an IMP-34-producing P. aeruginosa harboring two copies of bla(IMP-34) on its chromosome.